Identification of propagation methods for some species common to Albania and Southern Italy - Cocozza Talia M.A.; La Viola A.M.F. (Italo-Albanian cooperation for the enhancement of plant biodiversity, 2001)
Some preliminary results are given of a research caried out in order to develop the techniques of sexual and asexual propagation of species common to both countries such as: Fraxinus excelsior L., Myrtus communis L., Phlomis fruticosa L., Rosmarinus officinalis L., Sambucus nigra L. and Viburnum tinus L.. As for sexual propagation, several sowing periods were compared (from February to June) as well as pre-sowing treatments at a temperature of 5°C for different periods (from 0 to 6 days). Pertaining to the asexual propagation, a study was conducted on the impact of the date of cutting collection (from February to May), the type of cutting (herbaceous, semihardwood, hardwood); for each type, apical, central and basal cuttings were confronted. Results show that the sowing period impacts only the germination rate, whereas low temperature treatments increase the germination percentage. As to the asexual propagation, the various species gave a different response according to the period and type of cutting.
2. Seminar: Italo-Albanian cooperation for the enhancement of plant biodiversity, 2000/10/26-28, Tirana (Albania)